Performance improvement strategies of R1234yf in vapor compression refrigeration system as a R134a replacement : A review - M. Z., Sharif; Wan Hamzah, Azmi; Mohd Fairusham, Ghazali; Samykano, Mahendran; Ali, Hafiz Muhammad (Taiwan Institute of Chemical Engineers, 2023)
R1234yf, a substitute for R134a, shares similar thermodynamic behavior and eco-friendly properties with low global warming potential. However, performance and flammability issues hampered its adoption in vapor compression refrigeration systems (VCRS). This review examines diverse strategies implemented in R1234yf-based VCRS, including internal heat exchanger (IHX) utilization, ejector implementation, refrigerant charge optimization, HVAC component optimization, nanolubricant application, and R1234yf azeotropic mixture usage. Findings indicate significant enhancements in VCRS performance using R1234yf. IHX and precise condenser subcooling improve the coefficient of performance (COP). The ejector yields substantial performance gains of 4% to 23.29%. Increased refrigerant charge levels beyond the optimum enhance cooling capacity. Optimizing the compressor, expansion valve, and system parameters leads to notable improvements of 11.3% and 8% in cooling capacity and COP, respectively, for R1234yf-based systems. Nanolubricants yield noteworthy enhancements of up to 15.7% in cooling capacity and 9.8% in COP. Employing R1234yf azeotropic mixture effectively addresses flammability and performance concerns, albeit with a higher global warming potential (GWP). Further research is necessary to utilize lower GWP refrigerants in VCRS through various strategies efficiently.